Utilization of Digital Marketing through Social Media to Increase Sales for Entrepreneurs in the Malang Convection Sector - Hasyim, Hasyim; Rinca Eklesia Siringoringo; Thiovani Natalia Sitindaon; Lili Mutiana Rizky Handayani (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to analyze the use of digital marketing via social media to increase sales for entrepreneurs in the Malang Convection sector. This research uses a qualitative descriptive research method approach with data collection techniques, namely interviews and literature study. Utilizing digital marketing strategies through social media provides great opportunities for entrepreneurs in the bikiniaja_id convection sector in Malang to increase sales. By utilizing digital platforms such as Instagram, Facebook and Twitter, convection entrepreneurs can effectively promote their products to a wider audience. With the right digital marketing strategy, convection entrepreneurs in Malang can achieve sustainable sales increases, strengthen their brands, and achieve success in an increasingly digitalized business world.